Aluminium effect on aidification activity of buckwheat germinating roots - O. Smirnov; O. Kosyk; N. Taran (Vìsnik: Kiïvsʹkij Nacìonalʹnij Unìversitet Imenì Tarasa Ševčenka. Bìologìâ, 2016)
Integral indicators of common buckwheat (Fagopyrum esculentum Moench.) and tartary buckwheat (Fagopyrum tataricum Gaertn.) root cell H+-ATPase functional status – acidification activity and relative acidification activity under aluminium treatment were investigated. Inhibitory action of aluminium on germinating roots proton efflux and specific difference of relative acidification activity was revealed.